Singers performing kirtans and bhajans - Mumbai Archive Project Team (Jio Institute, 2024)
Singers assemble to perform kirtans and bhajans, devotional songs that praise and glorify the divine often recounting stories from Hindu mythology or expressing devotion and love for God. Kirtans are integral to Bhakti traditions and are seen as a powerful way to connect with the divine and experience a sense of oneness and unity with the universe.